Answer :
Answer: Each term of the equation can be multiplied by [tex]4[/tex] to eliminate the fractions before solving.
Step-by-step explanation:
Given the following expression:
[tex]-\frac{3}{4}m-\frac{1}{2}=2+\frac{1}{4}m[/tex]
You need to simplify before solve it.
Notice that the denominators are different, then you must find the Least Common Denominator (LCD).
Descompose the denominators into their prime factors:
[tex]4=2*2=2^2\\2=2[/tex]
Choose [tex]2^2[/tex], because it has the highest exponent. Then:
[tex]LCD=2^2=4[/tex]
Finally you can multiply on both sides by 4 in order to to eliminate the fractions before solving:
[tex](4)(-\frac{3}{4}m)-(4)(\frac{1}{2})=(4)(2)+(4)(\frac{1}{4}m)\\\\-3m-2=8+m[/tex]
Answer:
The Answer is 4
Step-by-step explanation:
I just did the Quiz on Edge